Genes y plásmidos de la Salmonella spp asociados con virulencia (2001)
ABSTRACT: The Salmonella species are intracellular facultative pathogens that affect several animals, including birds, pigs, cattle and humans. After ingestion of contaminated water or food, the bacteria reach the last portion of the small gut. These microorganisms need to express coordinately many of their genes in order to establish a productive infection. The expression begins when the bacteria get in contact with the hostile environment that represent the host gut tract, where they found a great variety of conditions such as: osmolality, oxygen tension and pH. These conditions induce the transcription of genes that codify virulence factors required during the pathogenesis. Additionally, the Salmonella uses a type III secretion system as a basic mechanism of virulence. Through this system a variety of unrelated proteins are secreted and translocated into the citosol of eukaryotic cells, interfer18 ing with the transduction signals and other cellular processes, favoring the bacteria pathogenesis. Some of these genes have been described and characterized by in vitro isolation of mutants, which have shown defects in several characteristics that might be important to carry out some basic functions and also for virulence; for instance: the capability to colonize epithelial cells in culture, the survival inside fagocitic cells, the regulation of inflammation processes and the secretion of fluids. Most of these genes that encode virulence factors are regulated by systems that can be found in both, pathogens and no pathogens species. Several strains of Salmonella have plasmids that encode virulence genes, which are highly associated with bacteremia and systemic infections. A better understanding of these genes, of their proteins products and their functions will improve our knowledge of the pathogenecity pathways used by these microorganisms when they infect a susceptible host. Additionally the development of strategies to successfully prevent such infections will be more easily accomplished.